Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Pembelian Pelumas Merek Fastron PT. Pertamina di Mempawah - Julianto . (JURNAL MANAJEMEN MOTIVASI, 2014)
The study examines the factors that can influence consumer behavior in purchasing brand lubricants Fastron PT. Pertamina in Mempawah. This is a descriptive study design and data collection techniques used for questionnaires and observation techniques. The samples in this study using purposive sampling and sample of 100 people. Analysis of the data used is the factor analysis and the data processed with the help of the Computer Program Statistics Package for Social Sciences (SPSS). The test results showed that the number of factors that are formed based on the Eigenvalues, percentage of variance, and the cumulative percentage of variance is as much as 7 (seven) factors, namely; factor of the mind, a factor of affordability, the price factor, quality factor, satisfaction factors, factors of knowledge about the brand, influence factor friend / sales with the high percentage of cumulative variation (cumulative percentage of variance) of 77.276%.